2021
DOI: 10.1536/ihj.20-309
|View full text |Cite
|
Sign up to set email alerts
|

Late Stent Thrombosis After Drug-Coated Balloon Coronary Angioplasty for In-Stent Restenosis

Abstract: A 41-year-old woman with chest pain for 6 hours was admitted to our chest pain center, presenting with acute myocardial infarction. Coronary angiography showed acute total occlusion in the proximal left anterior descending artery due to late stent thrombosis. After thrombus aspiration and intracoronary administration of 0.5 mg tirofiban, repeated angiography showed that no obvious residual stenosis remained. The patient underwent drug-coated balloon angioplasty 69 days ago and was then administered dual antipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…ISR is a major clinical problem after interventional therapy, which is mainly caused by coronary intimal hyperplasia, and oral administration alone to reduce the incidence of ISR is ineffective and has side effects [ 12 ]. Relevant studies have pointed out that DCB treatment for DES-ISR patients can improve the degree of in-stent stenosis [ 13 , 14 ]. It has also been reported that CBA can reduce the incidence of repeated ISR and have less lumen loss than ordinary high-pressure balloon preconditioning [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…ISR is a major clinical problem after interventional therapy, which is mainly caused by coronary intimal hyperplasia, and oral administration alone to reduce the incidence of ISR is ineffective and has side effects [ 12 ]. Relevant studies have pointed out that DCB treatment for DES-ISR patients can improve the degree of in-stent stenosis [ 13 , 14 ]. It has also been reported that CBA can reduce the incidence of repeated ISR and have less lumen loss than ordinary high-pressure balloon preconditioning [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A loading dose of 180 mg followed by a maintenance dose of 90 mg twice daily are recommended for patients with ACS, while a dose of 60 mg twice daily is recommended for long-term antiplatelet prophylaxis in high-ischemic-risk CAD patients [ 5 , 39 , 40 ]. Although a recent randomized study suggested better efficacy (with similar safety profile) of prasugrel compared to ticagrelor in ACS patients undergoing PCI [ 2 ], ticagrelor therapy had been repeatedly described as an effective approach for overcoming clopidogrel resistance [ 5 , 41 , 42 ] and is still preferred in those ACS patients who could not receive prasugrel.…”
Section: Novel-generation Adprbmentioning
confidence: 99%
“…The findings of two major randomized trials [9,10] establish that elective stent insertion is better for new pathological changes in balloon angioplasty for large coronary arteries (.3 mm). Though, nearly one-third of lesions in current practice are situated in narrow (3 mm) coronary arteries, [11,12] a status associated with poor prognosis after balloon angioplasty [13].…”
Section: Introductionmentioning
confidence: 99%